Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd007845.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Momordica charantia for type 2 diabetes mellitus

Abstract: Momordica charantia (bitter gourd) is not only a nutritious vegetable but it is also used in traditional medical practices to treat type 2 diabetes mellitus. Experimental studies with animals and humans suggested that the vegetable has a possible role in glycaemic control. To assess the effects of mormodica charantia for type 2 diabetes mellitus. Several electronic databases were searched, among these were The Cochrane Library (Issue 1, 2012), MEDLINE, EMBASE, CINAHL, SIGLE and LILACS (all up to February 2012)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 55 publications
1
57
0
4
Order By: Relevance
“…It is possible that the herbal therapies used for wellness by these adults are herbs used specifically for diabetes, but there is conflicting evidence or insufficient evidence for efficacy in diabetes. [8][9][10][11][12][13] Furthermore, the present study found that those using CAM for both treatment and wellness reported a twofold higher "better sense of control over their health" and "improved overall health and feeling better" than those who used CAM for treatment only. These measures could represent a proxy for healthrelated (HR) QoL.…”
Section: Fpl Federal Poverty Levelsupporting
confidence: 54%
“…It is possible that the herbal therapies used for wellness by these adults are herbs used specifically for diabetes, but there is conflicting evidence or insufficient evidence for efficacy in diabetes. [8][9][10][11][12][13] Furthermore, the present study found that those using CAM for both treatment and wellness reported a twofold higher "better sense of control over their health" and "improved overall health and feeling better" than those who used CAM for treatment only. These measures could represent a proxy for healthrelated (HR) QoL.…”
Section: Fpl Federal Poverty Levelsupporting
confidence: 54%
“…Momordica charantia (bitter melon) is a popular fruit used for the treatment of diabetes and related conditions amongst the indigenous populations of Asia, South America, India and East Africa. Many animal and human studies have proved the potential role of Momordica charantia in glycaemic control [66]. Momordica charantia reduces blood glucose levels and also significantly lowers the serum insulin levels in KK-Ay mice after 3 weeks of oral administration [67].…”
Section: Traditional Chinese Medicinesmentioning
confidence: 99%
“…The biases due to small studies effect, methodological flaws, use of inappropriate animal models of the human condition, use of unstandardized intervention, inappropriate use of statistics, and poor or selective reporting need immediate attention. Together, this systematic review and meta-analysis suggests that previous clinical trials of M. charantia L. could have been conducted based on inadequate evidence of efficacy from preclinical studies, and partly this could explains conflicting clinical trial results observed in the meta-analysis [20,120,121].…”
Section: Discussionmentioning
confidence: 98%